Construction and Research of Lightweight Cryptography SOPT-S Boxes Based on Inverse Mapping in Galois Field - Zhaolong Fan; Qijian Xu; Yongju Xu; Fei Wang (Dianxin kexue)
A new lightweight S boxes based on the inverse mapping in Galois field which called suboptimal-S boxes （SOPT-S boxes）with excellent performance in cryptology was constructed. It is shown that the SOPT-S boxes perform better in cryptographic properties such as differential uniformity, algebraic degree and avalanche effect than PRESENT, of which the algebraic degree achieves to n-1, avalanche effect to 1/2 and both of them achieve to the best, besides, it has an equivalent nonlinearity compared with PRESENT. In addition, the hardware overhead is also the same as the latter, so that it can provide a reference for the designing of nonlinear layer of lightweight cryptography algorithm.